Urban agriculture in Cape Town : an investigation into the history and impact of small-scale urban agriculture in the Cape Flats townships with a special focus on the social benefits of urban farming - Dunn, Shirley (Department of Historical Studies, 2014)
Includes bibliographical references (leaves 206-212).